Change and Continuity of Waste Management in Tourism Destination of Gili Trawangan, Indonesia: A Sociological Field Theory - Anugrah, Galang (Forum Ilmu Sosial, 2021)
This paper aims to analyze change and continuity of waste management in the tourism destination of Gili Trawangan after the waste crisis in 2017. By employing sociological field theory, using a case study method, and interviewing 13 key informants, this study comes to the following conclusions. The crisis brought about temporary instability in the waste management field, but simultaneously became a catalyst that led to change although there were things that remained stable as well. There are several changes: 1) mechanization of waste management facilities from traditional to modern; 2) implementation of regional regulations and changes in the position of the governance unit; 3) restructuring of waste management organizations from informal to formal business entities. However, despite the restructuration occurred, the informal networks that conditioning social relation in the field remains unchanged. Sociologically, it did not rupture the configuration of the existing social structure, where local business actors remained the dominant group in the Gili Trawangan. Therefore, the shocks caused by the crisis merely gave a little wave to the waste management field. All in all, learning from the case in Gili Trawangan, this paper offers practical recommendations for policymakers regarding waste management issues.